Effect of Obesity on Retinal Integrity in African Americans and Caucasian Americans With Relapsing Multiple Sclerosis - Rube, Jacob; Bross, Madeline; Bernitsas, Christopher; Hackett, Melody; Bao, Fen; Bernitsas, Evanthia (Frontiers in Neurology, 2021)
Abstract Objective: To study the effect of obesity on retinal structures in African Americans (AA) and Caucasian Americans (CA) with Relapsing Remitting Multiple Sclerosis (RRMS). Methodology: One hundred thirty-six RRMS patients without history of optic neuritis were divided into two groups, based on body mass index (BMI): 67 obese, (40 AA, 27 CA, mean BMI±SD: 36.7±5.8) and 69 non-obese (23 AA, 46 CA, mean BMI±SD: 24.0±3.1). The peripapillary retinal nerve fiber layer (pRNFL) thickness was quantified by OCT and was segmented into quadrant thickness: superior (S), inferior (I), temporal (T), nasal (N). Papillomacular bundle (PMB) thickness, retinal nerve fiber (RNFL), ganglion cell + inner plexiform (GCIPL), inner nuclear (INL), outer plexiform (OPL), outer nuclear (ONL) and total macular (TMV) volumes were obtained. Results: Obesity was associated with lower T thickness (58.54±15.2 vs 61.9 12.4, p=0.044), higher INL (0.98± 0.07 vs 0.96± 0.06, p=0.034) and lower RNFL (0.77±0.14 vs 0.82±0.12, p=0.009) volumes. Obese AA had significantly thinner T (58.54±15.19 vs 61.91±12.39, p=0.033), N (68.94±2.7 vs 77.94±3.3, p=0.044), TMV (8.15± 0.07 vs 8.52± 0.09, p=0.003), RNFL (0.74± 0.02 vs 0.82± 0.02, p=0.013), OPL (0.76±0.01 vs 0.79±0.1, p=0.050), ONL (1.68± 0.031 vs 1.79±0.038, p=0.026), and GCIPL (1.78± 0.04 vs 1.9±0.05, p=0.038) compared to obese CA. Among non-obese patients, the ONL was significantly lower in AA (1.78± 0.04 vs 1.9± 0.05, p<0.001). Conclusions: Obesity is associated with retinal structure abnormalities in RRMS patients. Its impact might be more prominent in AA than CA. Large longitudinal studies are needed to validate our findings.